Tetraalkoxylated-PPV derivative: An efficient and pure green electroluminescent polymer with good solution processability - Lee, Ji-Hoon; Kee, In-Seo; Kang, In-Nam; Son, Jhun-Mo; Kim, Kyu-Sik; Park, Moo-Jin; Hwang, Do-Hoon (Current applied physics, 2009)
A new solution-processable tetraalkoxy-substituted poly(1,4-phenylenevinylene) derivative, poly{[2-(3′,7′-dimethyloctyloxy)-3,5,6-trimethoxy]-1,4-phenylenevinylene} (TALK-PPV), was synthesized through a dehydrohalogenation polymerization route, and its light-emitting properties were investigated. The TALK-PPV showed highly blue-shifted UV–visible absorption and PL emission spectra compared to the dialkoxy-substituted PPV derivatives. This is because of the disturbance to the π-conjugation caused by a steric hindered structure. The TALK-PPV thin film exhibited an absorption peak at 446nm, with an onset at 515nm. Its PL emission maximum was at 554nm. Cyclic voltammetric analysis showed the HOMO and LUMO energy levels of the TALK-PPV to be 5.77 and 3.36eV, respectively. Light-emitting devices were fabricated with an ITO (indium-tin oxide)/PEDOT/polymer/Ca/Al configuration. The TALK-PPV component leads to pure green light emission with a CIE 1931 chromaticity of (0.20, 0.74) at 100cd/m2 brightness, which is very close to the standard green (0.21, 0.71) demanded by the NTSC (National Television System Committee). The maximum brightness of this device was 24,900cd/m2 with an efficiency of 1.45cd/A.